1 Loss of relationship: a qualitative study of families and caregivers after home-based palliative care ends. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Vierhout, Megan; Varenbut, Jaymie; Amos, Elizabeth; Buchman, Sandy; Goldman, Russell; Husain, Amna; Meuser, James; Bernstein, Mark
Abstract : Background: Home-based palliative care is care of the patient in the comfort of their own home, while doctors and other healthcare providers make visits as required. Family involvement naturally cultivates a relationship between healthcare providers and the family. Once the patient dies and care ends, this relationship is abruptly terminated, which may be challenging to both parties. This study explored healthcare providers' and family members' thoughts regarding the loss of relationship following home-palliative care, how to mitigate this loss, and their opinions on a system that allows for contact post patient death. Methods: Perceptions of 63 participants (32 healthcare providers and 31 family members) were explored using semi-structured interviews and qualitative research methodology, around three months after patient death. Healthcare providers were interviewed primarily at a home-based palliative physician group (TLCPC), and at two hospitals, while family members were recruited from the deceased patients of TLCPC physicians. Results: Six overarching themes emerged: Caregivers and families have a mutual appreciation and recognition of the intimacy of home-palliative care; both parties expressed awareness and dissatisfaction with the abrupt ending of relationship; open and clear communication with healthcare providers is beneficial to family members, especially after patient death; healthcare providers discern the insufficiency of resources and gap in transition to bereavement services for grieving families; a proposed system to mitigate loss of relationship has multiple perceived benefits; logistical challenges and boundary issues for a system raise concern in healthcare providers. Conclusions: The findings obtained in this study provide recognition of how caregivers and families perceive the dynamics of home-palliative care, and their thoughts regarding the loss of relationship. Overall, families and healthcare providers do not like this halt in contact, and recognise the potential benefits of an approach that would allow for communication going forward.